2018
DOI: 10.1007/s40430-018-1007-x
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady stagnation point flow of Oldroyd-B nanofluid with heat generation/absorption and nonlinear thermal radiation

Abstract: This article addresses unsteady stagnation point flow of Oldroyd-B nanofluid past an impermeable stretching sheet. Characteristics of heat transfer are described within the frame of heat generation/absorption and nonlinear radiative process. Intention in present analysis is to develop a model for nanomaterial containing Brownian motion and thermophoresis phenomena. The resulting nonlinear differential systems have been solved for the convergent homotopic solutions. Behavior of sundry variable for the velocity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The correlation of investigative outcomes is made with the current literature for the specific estimations of stream parameters. These correlations are shown in Table 1 with those of Hayat et al, 46 Pop et al, 49 and Hayat et al 50 The results are found in close concurrence with the current outcomes within acceptable limits.…”
Section: The Runge‐kutta‐gill Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The correlation of investigative outcomes is made with the current literature for the specific estimations of stream parameters. These correlations are shown in Table 1 with those of Hayat et al, 46 Pop et al, 49 and Hayat et al 50 The results are found in close concurrence with the current outcomes within acceptable limits.…”
Section: The Runge‐kutta‐gill Methodssupporting
confidence: 85%
“…Superficially, mutually the nanofluid and the pane are set at a steady temperature T w , here T T > w ∞ are utilized for the warmed extended float up, and T T < w ∞ relates to the frozen float up. The nanofluid coherence, force, energy, and nanoparticle division conditions can be communicated as 46 :…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts of symmetric/ asymmetric wall zeta potentials in electroosmotic flow of non-Newtonian (Oldroyd-B) liquid are elaborated by Kaushik and Chakraborty (2017). Further analyses covering Oldroyd-B liquid subjected to distinct configurations are given in Waqas et al (2017a); Alshomrani et al (2018); Waqas et al (2018c); Irfan et al (2018b); Hayat et al (2018).…”
Section: Introductionmentioning
confidence: 99%